2017
DOI: 10.1080/10428194.2017.1337115
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming multiple myeloma drug resistance in the era of cancer ‘omics’

Abstract: Multiple myeloma (MM) is among the most compelling examples of cancer in which research has markedly improved the length and quality of lives of those afflicted. Research efforts have led to 18 newly approved treatments over the last 12 years, including seven in 2015. However, despite significant improvement in overall survival, MM remains incurable as most patients inevitably, yet unpredictably, develop refractory disease. Recent advances in high-throughput 'omics' techniques afford us an unprecedented opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 108 publications
0
25
0
Order By: Relevance
“…In MM, initial lipidomic studies comparing malignant plasma cells to healthy plasma cells have reported decreased levels of phosphatidylcholines [8], and differing fatty acid composition of cellular membranes [8,9]. There are limited studies on the metabolic changes that occur during MM relapse, with most studies focusing at the genomic level [10]. Using Raman spectroscopy to compare between drug resistant and sensitive MM cell lines, Franco et al suggested differences in nuclear structure, as reflected by altered DNA:RNA ratio as well as cholesterol and phosphatidylethanolamine content [11].…”
Section: Competing Interestsmentioning
confidence: 99%
“…In MM, initial lipidomic studies comparing malignant plasma cells to healthy plasma cells have reported decreased levels of phosphatidylcholines [8], and differing fatty acid composition of cellular membranes [8,9]. There are limited studies on the metabolic changes that occur during MM relapse, with most studies focusing at the genomic level [10]. Using Raman spectroscopy to compare between drug resistant and sensitive MM cell lines, Franco et al suggested differences in nuclear structure, as reflected by altered DNA:RNA ratio as well as cholesterol and phosphatidylethanolamine content [11].…”
Section: Competing Interestsmentioning
confidence: 99%
“…Advanced mature B cell malignancies, including MM, represent a wide range of frequent cancers and are still considered incurable for many patients. Despite significant progress in understanding the pathogenesis of these malignancies, novel targeted therapies have been successful for only some subentities and specific scenarios (28). To develop alternative preclinical models, we here generated a mouse model on a C57BL/6 background where conditional L-gp130 activation was directed to the hematopoietic system at different developmental stages.…”
Section: Introductionmentioning
confidence: 99%
“…In MM, initial lipidomic studies comparing malignant plasma cells to healthy plasma cells have reported decreased levels of phosphatidylcholines [8], and differing fatty acid composition of cellular membranes [8, 9]. There are limited studies on the metabolic changes that occur during MM relapse, with most studies focusing at the genomic level [10]. Using Raman spectroscopy to compare between drug resistant and sensitive MM cell lines, Franco et al .…”
Section: Introductionmentioning
confidence: 99%